O TRABALHO DA GESTANTE OU LACTANTE EM AMBIENTE INSALUBRE NA REFORMA TRABALHISTA: AVANÇO OU RETROCESSO? (REMUNOM, 2023)
The present work aims to analyze the changes resulting from the Labor Reform in the work of pregnant and lactating women in unhealthy places. Through a demonstration of the legislative evolution that contemplates the right of the employed woman, the concepts of unhealthy conditions and the principles pertinent to the protection of the pregnant/lactating employee were pointed out and how the protection of these in relation to unhealthy work was given in the Brazilian legislation until the Labor Reform. From this context, ADI 5938 was analyzed, which judged the(un)constitutionality of the new art. 394-A of the CLT, as amended by Law 13.467/2017 (Labour Reform), which allowed pregnant women to work in unhealthy conditions in medium and minimum degrees and breastfeeding mothers in any degree, unless a medical certificate is presented that determines the removal of the work. At the end of the study, it was concluded that the current wording of article 394-A is a social setback, not only because the woman may not be aware of the law and, therefore, the attribution of this burden of seeking a certificate to move away can cause many cases to be neglected, but also because medicine is not an exact science and, at this point, the precautionary principle must prevail since protection is not only for the employed woman, but also for the one who does not have any option in the labor scenario: the son. Keywords: Labor Reform; Pregnant and lactating women; Unhealthy; ADI 5938.